Improving Educational Outcomes Through Adaptive Learning Systems using AI - Sari, Herva Emilda; Tumanggor, Benelekser; Efron, David (Pandawan Sejahtera Indonesia, 2024)
Adaptive learning systems powered by AI have transformed education by offering personalized learning experiences tailored to individual student needs, enhancing engagement and outcomes. This study examines the impact of AI-driven adaptive learning systems on educational outcomes across diverse settings using a mixed-methods approach. Quantitative data were collected through pre- and post-assessments, surveys, and system analytics, while qualitative insights were obtained via interviews. Participants included 300 students and 50 educators spanning primary to higher education. Findings revealed a substantial improvement in student performance, with average post-assessment scores increasing from 68.4 to 82.7. AI tools such as Smart Sparrow and IBM Watson Education demonstrated higher course completion rates and increased student engagement. Comparative analysis confirmed the superior effectiveness of adaptive systems over traditional methods. These results highlight the potential of AI-driven systems to enhance educational quality and equity. The study also identifies challenges, including institutional technical readiness, educator training, and infrastructural needs, which are critical for successful implementation. Future research should explore long-term impacts, algorithmic optimization, and ethical considerations, addressing issues such as potential biases and data privacy concerns. Standardizing references, citations, and formatting is recommended to ensure professional presentation. By examining the practical barriers and offering insights into their resolution, this research provides a foundation for the broader adoption of adaptive learning systems, underscoring their transformative potential in creating inclusive and effective educational environments. These findings advocate for continued exploration and development of AI-driven tools to advance learning outcomes globally.